Assessment of antibiotic utilization patterns in an Indian Level-1 Trauma Center: a pilot study exploring days of antibiotic spectrum coverage and defined daily doses using WHO AWaRe classification trends - Ahmed, M Nizam; Thakur, Arpan Kumar; Srivastava, Smriti; Ningombam, Aparna; Kirti, Madhavi; Sagar, Sushma; Goyal, Keshav; Kumar, Subodh; Bindra, Ashish; Singh, Gyaninder Pal; Sokhal, Navdeep; Aggarwal, Richa; et al. (Frontiers in Antibiotics, 2025)
BackgroundRising antimicrobial resistance (AMR) necessitates innovative metrics, such as days of antibiotic spectrum coverage (DASC), to optimize antibiotic stewardship. This study evaluated antibiotic use in an Indian trauma center using DASC, defined daily doses (DDD), and the World Health Organization (WHO) Access, Watch, Reserve (AWaRe) classification.MethodsThis retrospective cohort study analyzed data from 1,812 adult inpatients (mean age: 35 years; 70% male; 80% with polytrauma) admitted to a 250-bed Level-1 Trauma Center at the All India Institute of Medical Sciences (AIIMS), India, from August to October 2022. We measured days of therapy (DOT), DDD, and DASC for 46 antibiotics across 12 pathogens [e.g., methicillin-susceptible Staphylococcus aureus (MSSA), carbapenem-resistant Enterobacteriaceae]. DASC scores were developed through expert consensus and local antibiogram data, and validated using Pearson’s correlation with DOT (R = 0.43, p < 0.1) and DDD (R = 0.21). Differences in antibiotic usage between the ICU and ward were analyzed using a t-test in R software.ResultsTotal antibiotic consumption was 81,064.6 g (3,142 DDD/1,000 patient-days). The Watch group antibiotics dominated usage (37%, 16,018.6 g), resulting in a low Access-to-Watch ratio (0.47). ICU settings showed higher DDD values (326 vs. 193/1,000 patient-days, p < 0.05) and DASC/DOT ratios (mean: 3; 95% CI: 2.73–4.01). Piperacillin–tazobactam accounted for the largest share of the Watch category use (5,952.9 g). DASC values (mean 4401.5, 95% CI: 3592-5211.1) showed a moderate correlation with DOT (R = 0.43, p < 0.1), offering spectrum-specific insights.ConclusionsExcessive use of the Watch group antibiotics contributes significantly to AMR. However, DASC’s novel, spectrum-focused approach offers a transformative tool for antibiotic stewardship, supporting targeted de-escalation and improved benchmarking. These findings underscore the urgent need for policy reforms to enforce adherence to the WHO AWaRe classification in Indian centers, potentially reducing AMR-related mortality (30% higher with resistant infections). Integrating DASC into global Antimicrobial stewardship (AMS) programs may redefine antibiotic prescribing practices and help mitigate the AMR crisis.